Social and behavioral determinants in public health: current perspectives - Haliza Mohd. Riji (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
This paper highlights the importance of recognizing behavioral determinants in public health. Public health has evolved over the decades from those that focused on disease prevention to the all encompassing health promotion which places the interactive nature of participating components. Public health occurs within cultural contexts within which social and behavioral factors play important roles. Though it has long been recognized that people's socioeconomic status, attitude and behavior hinder them from using the health services, the challenge to bring forth greater equity and centrality of people in public health remains to be realized. In the meantime, health professionals have to increase their health literacy - knowing and learning more about the people's perspectives. Topics of past and current importance that require more concern and research in public health are compliance, stigma, gender, health education messages. Finally, a call for multidisciplinary approaches in public health is made.